Propagandist use of history and archaeology in justification of Polish rights to the “Recovered Territories” after World War II - Kobyliński, Zbigniew; Rutkowska, Grażyna (1956–2019) (Institute of Archaeology and Ethnology Polish Academy of Sciences, 2005)
Analysis of the daily newspapers published in Poland in the post-War period allows to contribute in an objective way to the ongoing debate on the role which archaeology played in the politics in the period of Communist government. Local newspapers from Silesia and Lubusz Land as well as the central daily paper of the Central Committee of the Communist Party were analyzed for the period before 1970 to find out if archaeology and history were used in an anti-German propaganda and in justification of the Polish rights to the Western Territories regained after the World War II
il. ; 24 cm
Keywords: Ziemie Odzyskane; Śląsk; Lubuska Ziemia; polsko-niemieckie stosunki; propaganda; archeologia; prasa codzienna